Proportion and Factors Associated with Zinc Deficiency in Acute Diarrhea Patients - Budi Tan Oto; Marcellus Simadibrata; Drupadi Harnopidjati Singh Dillon; Siti Setiati (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: Zinc may affect the intestinal immune response. No data has been available on zinc deficiency in adult patients with diarrhea, especially for Indonesian population. Zinc metabolism, etiologies, pathogenesis and clinical course of diarrhea may have various effects on zinc concentration in different population. This study aimed to determine the proportion of zinc deficiency in patients with acute diarrhea, including its associated factors. Method: A cross-sectional study was conducted in patients with acute diarrhea at outpatient clinics and emergency wards of four hospitals between August 2010 and March 2011. A serum zinc concentration of 10.7 µmol/L was set as cut-off value for zinc deficiency. Data was analyzed by using Chi-square test. Results: There were 101 subjects, 54.5% were female, the median age was 26 years, median duration of acute diarrhea was 5 days, and the median frequency was 6 times/day. About 95% patients had nutritional status of subjective global assessment (SGA) A and the mean value of body mass index was 19.3 ± 0.70 kg/m2. Approximately 88.1% patients had severe infective diarrhea based on hydration status. About 69.3% patients were zinc deficient with the mean serum zinc concentration of 9.26 ± 2.95 µ mol/L. We found a significant correlation between the severity of diarrhea and zinc deficiency in patients with acute diarrhea. Conclusion: The proportion of zinc deficiency in acute diarrhea patients was quite large although the mean serum zinc level was still below the National Health and Nutrition Examination Survey (NHANES) reference value. The severity of diarrhea has been proven to be significant that affects zinc deficiency in acute diarrhea patients. Keywords: zinc deficiency, acute diarrhea, adult